2019
DOI: 10.22435/jki.v9i1.1100
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Infusion of Syzygium polyanthum (Wight) Walp. Leaves as Natural Preservative Chicken Meats

Abstract: Syzygium polyanthum (Wight) Walp. (Indonesian bay leaf) is known for possessing antimicrobial activity that might be applied for natural food preservative. In this study, we analyzed the constituents of infusion of S. polyanthum leaves and evaluated its potency as the preservative of fresh chicken meats. The infusions were prepared with the method described in Indonesian Pharmacopeia. Phytochemical content of infusion of S. polyanthum leaves was analyzed by qualitative phytochemical screening using colorimetri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
0
4
0
1
Order By: Relevance
“…The 20% bay leaf WE showed higher OD than those of the lower concentrations, which might be related to the nature of the obtained extract. A study reported that bay leaf WE contains flavonoids, tannins, and saponins, which effectively reduced the microbial growth on chicken meats during refrigerated storage at the optimum concentration of 10% (Hartanti et al, 2019). Tannins, as the large-molecule polyphenols, are brown in colour and have absorption with a wavelength of around 600 nm (Hassanpour et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 20% bay leaf WE showed higher OD than those of the lower concentrations, which might be related to the nature of the obtained extract. A study reported that bay leaf WE contains flavonoids, tannins, and saponins, which effectively reduced the microbial growth on chicken meats during refrigerated storage at the optimum concentration of 10% (Hartanti et al, 2019). Tannins, as the large-molecule polyphenols, are brown in colour and have absorption with a wavelength of around 600 nm (Hassanpour et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Bay leaf WE were prepared based on the procedure described in Hartanti et al (2019). First, the powdered plant materials were weighed and put in a classical infusion pot.…”
Section: Preparation Of Bay Leaf Water Extractmentioning
confidence: 99%
See 1 more Smart Citation
“…Semakin padat larutan, semakin besar hambatan tersebut. Nilai OD diukur pada skala 0 hingga 2, di mana OD 0 biasanya menunjukkan larutan kosong atau bersih (tanpa hambatan cahaya), sementara OD 2 menunjukkan larutan yang sangat padat dengan sel atau partikel (Hartanti et al, 2019).…”
Section: Gambar 1 Isolat Bakteri Termofilik Ms-12unclassified
“…At the optimal concentration of 10%, S. polyanthum leaf infusion can inhibit bacteria growth on chicken meat during storage, extending its shelf life by up to three days at 3-7 • C. [197] Shrimp and chicken Extract Dilution…”
Section: Food Antimicrobial Preservativementioning
confidence: 99%